Meckel–Gruber Syndrome: a population-based study on prevalence, prenatal diagnosis, clinical features, and survival in Europe - Barisic, Ingeborg (Eur J Hum Genet, 2015)
Meckel–Gruber Syndrome is a rare autosomal recessive lethal ciliopathy characterized by the triad of cystic renal dysplasia, occipital encephalocele and postaxial polydactyly. We present the largest population-based epidemiological study to date using data provided by the European Surveillance of Congenital Anomalies (EUROCAT) network. The study population consisted of 191 cases of MKS identified between January 1990 and December 2011 in 34 European registries. The mean prevalence was 2.6 per 100 000 births in a subset of registries with good ascertainment. The prevalence was stable over time, but regional differences were observed. There were 145 (75.9%) terminations of pregnancy after prenatal diagnosis, 13 (6.8%) fetal deaths, 33 (17.3%) live births. In addition to cystic kidneys (97.7%), encephalocele (83.8%) and polydactyly (87.3%), frequent features include other central nervous system anomalies (51.4%), fibrotic/cystic changes of the liver (65.5% of cases with post mortem examination) and orofacial clefts (31.8%). Various other anomalies were present in 64 (37%) patients. As nowadays most patients are detected very early in pregnancy when liver or kidney changes may not yet be developed or may be difficult to assess, none of the anomalies should be considered obligatory for the diagnosis. Most cases (90.2%) are diagnosed prenatally at 14.3±2.6 (range 11–36) gestational weeks and pregnancies are mainly terminated, reducing the number of LB to one-fifth of the total prevalence rate. Early diagnosis is important for timely counseling of affected couples regarding the option of pregnancy termination and prenatal genetic testing in future pregnancies.